Modern optics and photonics : atoms and structured media - Gurzadi͡an, G. G. (Gagik Grigorʹevich), 1957-; Kryuchkyan, Gagik Yu; Papoyan, Aram V. (World Scientific Pub. Co., 2010)
This volume is based on the works presented at the conference "Modern Problems in Optics and Photonics-2009", held in Yerevan, Armenia. Covering virtually all actual themes in Optics : Structured media and quantum nanostructures, Quantum optics and quantum information, Spectroscopy and dynamics of atoms, both theoretical and experimental worksare examined and discussed extensively. This volume would capture the interest of experienced scientists as important, original results of 27 leading researchers from Armenia, Australia, Germany, Greece, India, Latvia, Russia, Singapore and United Kingdom are included. Surely, this volume could serve as an advanced textbook for graduate and undergraduate students as it contains not only the original works of prominent authors, but also detailed introductions and descriptions of early results of the presented branches of the optics.